The Effect of Liquid Smoke Addition Presto Milkfish (Chanos chanos) Towards Consumer Acceptance - Putra, Erenno Akbari; Leksono, Tjipto; Desmelati, Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract This research was aimed to determine method and liquid smoke concentracion on presto milkfish  towards consumer acceptance that covers appearance, aroma, flavor, and texture. To know chemical content which were: water content, total acid content, total phenol content, and pH. Research was done with experiment method, that was to make presto milkfish with different coconut shell smoke liquid. Design used in this research was non factorial completely randomized design. The treatmens were addition of smoke liquid on presto milkfish with different amounts, with 4 treatments which were 0 ml (A0), 5 ml (A5), 10 ml (A10), and 15 ml (A15) smoke liquid addition. Reptiotion treatment was three times and the unit on this research was 12 units. Research result addition of different liquid smoke (0 ml, 5 ml, 10 ml, 15 ml) did not have real effect towards color, aroma, flavor and texture value of presto milkfish. Addition of 5 ml liquid smoke in each 200 gr milkfish was the best treatment to produced highest quality of presto milkfish. Charaecteristic of milkfish containts 30.04% water content, 9.89 total phenol, and 2.90 pH value. Keywords: Presto, milkfish (Chanos chanos), consumer acceptance.